From Access To Action: How Technology Accessibility And Communication Quality Drive Agricultural Productivity In Serdang Bedagai - Arsyad, Muhammad; Lubis, Yusniar; Effendi, Ihsan (Amkop Management Accounting Review (AMAR), 2026)
This research seeks to examine the impact of technology accessibility on agricultural output, mediated by the quality of communication in Serdang Bedagai Regency, North Sumatra Province. This research employed a quantitative methodology, utilizing a structured survey as the principal instrument for data collection. The target demographic comprised farmers engaged in agricultural training programs and extension services, with a sample size of 123 respondents who fulfilled the inclusion criteria. This criterion mandated that respondents be active farmers engaged in the utilization of agricultural technology within their farming methods. The reason for choosing this sample was that farmers who used technology were more likely to give useful information on how communication quality affects agricultural productivity. The findings indicated that technology accessibility enhanced agricultural productivity, with communication quality serving as a crucial intermediary in facilitating comprehension and successful application of technical information. Clear, open, and two-way communication was very important for helping people modify their behavior and adopt new ways of doing things in farming. These results show that agricultural development initiatives should put more emphasis on making technology more accessible, providing training based on requirements, and developing communication skills to help farmers become more productive and secure food supplies in the long term.